Molecular Building Blocks for Nanotechnology From Diamondoids to Nanoscale Materials and Applications - Mansoori, G.Ali.; Mansoori, G.Ali.; George, Thomas F.; George, Thomas F.; Assoufid, Lahsen.; Assoufid, Lahsen.; Zhang, Guoping.; Zhang, Guoping. (Topics in Applied Physics,, 2007)
This book is a result of the research and educational activities of a group of outstanding scientists worldwide who have authored the chapters of this book dealing with the behavior of nanoscale building blocks. It contains a variety of subjects covering computational, dry and wet nanotechnology. The state-of-the-art subject matters presented here provide the reader with the latest developments on ongoing nanoscience and nanotechnology research from the bottom-up approach, which starts with with atoms and molecules as molecular building blocks.